2003
DOI: 10.1002/art.10830
|View full text |Cite
|
Sign up to set email alerts
|

Are environmental factors important in primary systemic vasculitis?: A case–control study

Abstract: Objective. To investigate the association between primary systemic vasculitis (PSV) and environmental risk factors.Methods. Seventy-five PSV cases and 273 controls (220 nonvasculitis, 19 secondary vasculitis, and 34 asthma controls) were interviewed using a structured questionnaire. Factors investigated were social class, occupational and residential history, smoking, pets, allergies, vaccinations, medications, hepatitis, tuberculosis, and farm exposure in the year before symptom onset (index year). The Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
5
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 33 publications
5
141
5
4
Order By: Relevance
“…One report shows a higher prevalence of smoking in patients with ANCA-associated nephritis (19). On the other hand, there are studies showing no association between smoking status and ANCA-associated vasculitis (20,21). Thus, we could not determine whether the smoking habit influenced ANCA positivity in the present case.…”
Section: Discussioncontrasting
confidence: 56%
“…One report shows a higher prevalence of smoking in patients with ANCA-associated nephritis (19). On the other hand, there are studies showing no association between smoking status and ANCA-associated vasculitis (20,21). Thus, we could not determine whether the smoking habit influenced ANCA positivity in the present case.…”
Section: Discussioncontrasting
confidence: 56%
“…2 However, descriptive epidemiological studies identifying geographic variation, and other studies identifying seasonal differences in WG onset, have suggested that environmental factors also play a role in WG etiology. [2][3][4][5][6][7][8][9][10] Environmental exposures can affect ANCA production. For example, persons with chronic exposure to ambient silica more commonly have elevated serum ANCA titers with MPO antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, the results of several case-control studies have suggested that occupational history of inhaled ambient silica is a risk factor for developing AAV. [5][6][7][8] Other case-control studies have observed an association between exposure to metals, solvents, and pesticides and AAV occurrence. 8,11,12 While studies have identified the contribution of smoking to the development of rheumatoid factor and seropositive rheumatoid arthritis, studies of other immune-mediated disorders have failed to identify a clear influence of cigarette smoking on their development.…”
Section: Introductionmentioning
confidence: 99%
“…Although studied in a small number of patients, exposure to silica particles has also been considered a risk factor for EGPA, as it was for other VAA [27,28].…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%